2010
DOI: 10.1017/s0033291710001418
|View full text |Cite
|
Sign up to set email alerts
|

The role of mental disorders in the risk and speed of transition to alcohol use disorders among community youth

Abstract: Background. Among adolescents and young adults with DSM-IV alcohol use disorders (AUDs), there are interindividual differences in the speed of transition from initial alcohol use (AU) to AUD. AUDs are highly co-morbid with other mental disorders. The factors associated with rapid transition from first AU to AUD remain unknown and the role of mental disorders in rapid transitions is unclear. Given this background we examined (1) whether prior anxiety, mood, externalizing and non-alcohol substance use disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 67 publications
2
28
0
Order By: Relevance
“…For example, using data from a longitudinal study of adult male twins, cannabis initiation has been shown to be predicted by high genetic risk for problem cannabis use, high genetic risk of externalizing disorder, high sensation seeking personalities, low parental monitoring, high peer group deviance, and cannabis availability (Gillespie, Lubke, Gardner, Neale, & Kendler, 2012). In another community-based longitudinal study, early initiation of alcohol and nicotine use were associated with early initiation of cannabis use; however, only the association with nicotine use remained after controlling for externalizing disorders and parental substance dependence (Behrendt et al, 2012). This study also demonstrated that early initiation of alcohol and cannabis, paternal alcohol dependence, and externalizing disorders were associated with cannabis use and a higher risk of developing cannabis use disorders.…”
Section: Etiology Of Cannabis Use Disordersmentioning
confidence: 50%
“…For example, using data from a longitudinal study of adult male twins, cannabis initiation has been shown to be predicted by high genetic risk for problem cannabis use, high genetic risk of externalizing disorder, high sensation seeking personalities, low parental monitoring, high peer group deviance, and cannabis availability (Gillespie, Lubke, Gardner, Neale, & Kendler, 2012). In another community-based longitudinal study, early initiation of alcohol and nicotine use were associated with early initiation of cannabis use; however, only the association with nicotine use remained after controlling for externalizing disorders and parental substance dependence (Behrendt et al, 2012). This study also demonstrated that early initiation of alcohol and cannabis, paternal alcohol dependence, and externalizing disorders were associated with cannabis use and a higher risk of developing cannabis use disorders.…”
Section: Etiology Of Cannabis Use Disordersmentioning
confidence: 50%
“…Consistent with previous prospective studies examining if diagnostic-level SP during middle adolescence predicts later alcohol use (Behrendt et al, 2011;Buckner et al, 2008;Crum and Pratt, 2001;Zimmermann et al, 2003), we hypothesized that (a) baseline SP symptoms would predict increased odds of alcohol use throughout middle adolescence and (b) SP symptoms measured annually would prospectively predict increased odds of alcohol use over time from late childhood through middle adolescence.…”
mentioning
confidence: 62%
“…For example, one study demonstrated that SP at age 16 was associated with a 4.5 times greater likelihood of meeting criteria for alcohol dependence at age 30 (Buckner et al, 2008), whereas another study indicated that among adolescents and young adults, SP at baseline (age 14-24) predicted the persistence of alcohol dependence between baseline and follow-up (4 years later) as well as the onset of regular and hazardous alcohol use at follow-up (Zimmerman et al, 2003). Importantly, only SP and externalizing disorders at baseline were associated with more rapid transition from alcohol use to alcohol dependence; bipolar disorder, panic attacks, nicotine dependence, and problematic cannabis use were not associated with this transition (Behrendt et al, 2011). Thus, there is compelling evidence to suggest that an SP diagnosis places individuals at increased risk for alcohol use, alcohol dependence, and persistence of AUDs over time.…”
mentioning
confidence: 98%
“…An early onset of use of a specific substance is a risk factor for disorders related to that substance (Behrendt, Wittchen, Hofler, Lieb, & Beesdo, 2009;Dawson, Goldstein, Chou, Ruan, & Grant, 2008;Grucza, Norberg, Bucholz, & Bierut, 2008;Pitkanen, Lyyra, & Pulkkinen, 2005), although this effect has not been proved across substance classes. In contrast, a younger age at first alcohol use has been associated with increased risk of cannabis use (Behrendt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%